Spatial and temporal analysis of shared bicycle use in Limassol, Cyprus - Maas, Suzanne; Nikolaou, Paraskevas; Attard, Maria; Dimitriou, Loukas (My University, 2021)
Cities around the world are moving away from the car-centric infrastructure, urban design and planning policies prevalent since the 1950s and promoting sustainable mobility as an alternative, including cycling. As such, Bicycle Sharing Systems (BSS) have emerged as a transport innovation across the globe. Cycling modal share however remains low in most Southern European island cities. These cities exhibit certain characteristics considered as barriers to cycling, such as hot summers and high humidity, hilliness, and car-oriented culture and infrastructure. Despite this, BSS and policies promoting cycling have emerged in this region as well. These have the potential to provide alternatives for those marginalized by car-based mobility and to reduce traffic related diseases and injuries, noise and air pollution, which can contribute to an improved quality of life for all citizens. Using the Mediterranean island city of Limassol (Cyprus) as a case study, the utilization of bicycle sharing is investigated by constructing regression models to assess the influence of spatial and temporal factors on the demand for BSS use at stations. From the regression models it appears that land use factors such as residential, commercial and park land use, as well as the presence of the beach and cycling paths positively influences frequency of use, as does higher network connectivity. While higher tourist arrivals have a positive effect, the presence of hotels in a 300 m buffer around the stations does not. Higher rainfall, as well as higher temperatures, are associated with a decrease in BSS use. Explicitly incorporating spatial dependence, in Spatial Auto-Regressive (SAR) models, led to the formulation of models with comparable or better explanatory power, when compared to the Ordinary Least Squares (OLS) models. The insights from the regression models can be used to inform policies promoting cycling and the design and planning of BSS (expansion) in Limassol and other cities.
Keywords: Bicycle sharing; Cycling; Spatial analysis; Island sustainable mobility; Cyprus